2007
DOI: 10.1021/jp067581k
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Solution Behavior among Four Semiconductor-Binding Peptides

Abstract: Recent experiments have identified peptides with adhesion affinity for GaAs and Si surfaces. Here we use all-atom Monte Carlo (MC) simulations with implicit solvent to investigate the behavior in aqueous solution of four such peptides, all with 12 residues.At room temperature, we find that all the four peptides are largely unstructured, which is consistent with experimental data. At the same time, we find that one of the peptides is structurally different and more flexible, compared to the others. This finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
(77 reference statements)
1
13
0
4
Order By: Relevance
“…In recent computational analyses of the solvent properties of these peptides, we have shown that also the folding behaviors in solution exhibit noticeable differences. [27] This is also true at room temperature, where in both cases the population of the structurally different native folds is rather small. silicon substrate.…”
Section: àE(x)/rtmentioning
confidence: 90%
“…In recent computational analyses of the solvent properties of these peptides, we have shown that also the folding behaviors in solution exhibit noticeable differences. [27] This is also true at room temperature, where in both cases the population of the structurally different native folds is rather small. silicon substrate.…”
Section: àE(x)/rtmentioning
confidence: 90%
“…In jüngsten Computeranalysen der Eigenschaften dieser Peptide in Lösung haben wir gezeigt, dass das Faltungsverhalten in Lösung ebenfalls bemerkenswerte Unterschiede aufweist. [27] Dies gilt auch für Raumtemperatur, bei der in beiden Fällen die Besetzung der strukturell verschiedenen Grundzustandsfaltungen eher klein ist.…”
unclassified
“…[27] Die mutierte Sequenz S1' unterscheidet sich von S1 nur durch den Austausch von Prolin an Position 4 und Threonin an Position 9 (Abbildung 3 a). Entsprechend wurde S3' aus S3 abgeleitet, indem Prolin an Position 9 und Asparaginsäure an Position 4 ausgetauscht wurden (Abbildung 3 a).…”
unclassified
See 2 more Smart Citations